Urban greenspace as a climate change adaptation strategy for subtropical Asian cities: A comparative study across cities in three countries. (May 2021) - Mabon, Leslie; Shih, Wan-Yu
Highlights: Comparison of nature-based climate adaptation across subtropical Asian cities; Dense urban form and diverse governance structures in Asian cities compared to West; Competences as organising framework to assess policy and skills for adaptation; Capability to link government departments and sectors of society vital; Further research needed for normative competence under different governance forms. Abstract: Interest in nature-based approaches for climate change adaptation in cities is growing. Whilst there is a growing field of scholarship in a European and North America setting, research on the policy and governance of urban greenspace for climate adaptation in subtropical Asia is limited. Given the different development patterns, environmental characteristics and governance arrangements in subtropical cities, plus their comparatively large population and high climate risk, this is a significant knowledge gap. In response, this paper evaluates competences – skill sets, capabilities, and supporting policy and legislation – to enact adaptation through greenspace across different governance contexts; and assesses how international rhetoric on nature-based adaptation becomes localised to subtropical Asian city settings. We conduct interviews with stakeholders, plus review of relevant policy and city-specific research, for three cities with different governance and development contexts: Hanoi (Vietnam); Taipei (Taiwan); and Fukuoka (Japan). Across all three cases, we find that institutional structures and processes for connecting different remits and knowledge systems are a bigger challenge than a lack of appropriate policy or individuals with the required technical knowledge. However, opportunities for civil society participation and consideration of justice issues vary between the cities according to the socio-political context. These findings illustrate the value of individuals and organisations able to work across institutional boundaries in linking greenspace and adaptation agendas for subtropical Asian cities; and the importance of competence in collaboration with developers and civil society so that the rapid development or regeneration seen in subtropical Asian contexts does not tend towards green climate gentrification. More broadly, our findings show that the diverse nature of subtropical Asian cities means the role of greenspace in climate adaptation is likely to be context-specific, and thus that caution must be exercised against uncritically importing best practices from exemplar cases elsewhere.